How Salmonella infection can inform on mechanisms of immune function and homeostasis - Constantino Lopez-Macias (Frontiers Research Topics, 2016)
The use of model antigens such as haptens and ovalbumin has provided enormous insights into how immune responses develop, particularly to vaccine antigens. Furthermore, these studies are overwhelmingly performed in animals housed in clean facilities and are not known to have experienced overt clinical signs caused by infectious agents. Therefore, this is unlikely to reflect the impact more complex host-pathogen interactions can have on the host, nor the diversity in how immunity is regulated. Humans develop immune responses in the context of the periodic exposure to multiple pathogens and vaccines over a life-time. These are likely to have a long-lasting effect on who and what we are and how we respond to further antigen challenge. Therefore, studies on how infection influences immune homeostasis and how the development of responses to a pathogen reflects what is known on immune regulation will be informative on how we can translate findings from our standard models into treatments usable in humans. One organism allows us to do just this. Bacteria of the genus Salmonella are devastating human pathogens. Nevertheless, many aspects of the diseases they cause can be successfully modelled in murine systems so that the infection is either resolving or non-resolving. This has the advantage of allowing the long-term impact of infection on immune function to be assessed. We propose to welcome key workers to write about their research that examine the consequence of Salmonella infection on the host and the elements of the bacterium that contribute to this.